A study of defect analysis in medium cost apartment / Richeal Anak Andrice - Anak Andrice, Richeal (Faculty of Architecture, Planning and Surveying, 2013)
Building defects always have been a big problem for multi-storey residential building. Common defect that always occurring on this residential building such as crack, leakage, vandalism, algae, corrosion, peeling paint and many more. This defect happens because of different factor and reason. Some of the defect causes by weather, human activities, soil movement and etc. This research was aimed to identify types of defect and their causes. After that we will know the best remedial action for repair and prevent this defect to happen again. Other than that this study also aimed to find out the maintenance programme that prepared by maintenance department each apartment in maintaining their building. Too find all the data and information for my study, conduct the condition survey at each apartment is the best way to find types of defect that occurring on every apartment. Besides that interviewing session will be conduct by author, and the author target is all the maintenance staff at my case study. The question is more about defect and maintenance programme that they used for their building. It also asked how maintenance manager prepare the maintenance schedule and how their staff works.